Canadian Journal of Political Science / Revue canadienne de science politique (JSTOR)
The journal publishes outstanding scholarly manuscripts on all areas of political science, including the history of political thought, contemporary political theory, international relations and foreign policy, governmental institutions and processes, political behavior, public administration and public policy.
Keywords: Business, Business & Economics, Economics, Political Science, Social Sciences